NILAI-NILAI KEMANUSIAAN DALAM NOVEL SAGA DARI SAMUDRA KARYA RATIH KUMALA: KAJIAN SOSIOLOGI SASTRA - Anitalia Stefany Welayana (University of Brawijaya, 2024)
This research focuses on the study of literary sociology. Using the novel Saga dari Samudra by Ratih Kumala, will be studied influence of social background in the story based on problems of human life. Specifically, problems will be limited to human relationships with themselves and from outside. After analysis, it was found that parenting patterns and upbringing from the family and environment influence human traits and attitudes in acting. In general, individual behavior can be seen from human relationship with themselves, human relationships with others–including human, animal and plant, also human relationship with God. Individuals who have good relationships with others can adapt easily to every location they live. Apart from that, have a mature mindset and an open mind. He can also accept and respect opinions that differ from his own.